Promoting peaceful Islam: Strengthening religious moderation and P/CVE strategies for Indonesian female migrant workers - Tandos, Rosita (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2025)
Purpose – The purpose of this study was to examine the involvement and vulnerability of Indonesian female migrant workers (FMWs) in violent extremism and terrorism, as well as to explore their potential role in promoting peaceful Islamic values as a counter-narrative. Method – The population of this study consisted of 100 Muslim women who were formerly migrant workers. Data collection was conducted through a survey of all participants and in-depth interviews with 15 respondents using open-ended questions. The data were analyzed descriptively to identify patterns of vulnerability and opportunities for empowerment. Result – The results showed that some Indonesian FMWs have been targeted and even recruited by extremist groups. However, the findings also indicate that with proper empowerment, FMWs can serve as agents of peace, strengthening religious moderation both domestically and internationally. Implication – This study suggests the need for systematic programs that reinforce peaceful Islamic narratives, resilience, and empowerment among migrant communities as part of preventing and countering violent extremism (P/CVE). Originality/Value – This research provides one of the first empirical insights into the nexus between female migrant workers and violent extremism in Indonesia, highlighting their strategic role as peacebuilders in P/CVE efforts. *** Tujuan – Tujuan studi ini adalah untuk mengkaji keterlibatan dan kerentanan pekerja migran perempuan Indonesia (PMPI) dalam ekstremisme kekerasan dan terorisme, serta mengeksplorasi peran potensial mereka dalam mempromosikan nilai-nilai Islam yang damai sebagai narasi alternatif. Metode – Populasi studi ini terdiri dari 100 perempuan Muslim yang pernah menjadi pekerja migran. Pengumpulan data dilakukan melalui survei terhadap semua peserta dan wawancara mendalam dengan 15 responden menggunakan pertanyaan terbuka. Data dianalisis secara deskriptif untuk mengidentifikasi pola kerentanan dan peluang pemberdayaan. Hasil – Hasil penelitian menunjukkan bahwa beberapa FMW Indonesia telah menjadi sasaran dan bahkan direkrut oleh kelompok ekstremis. Namun, temuan juga menunjukkan bahwa dengan pemberdayaan yang tepat, FMW dapat berperan sebagai agen perdamaian, memperkuat moderasi agama baik secara domestik maupun internasional. Implikasi – Studi ini menyarankan perlunya program sistematis yang memperkuat narasi Islam yang damai, ketahanan, dan pemberdayaan di kalangan komunitas migran sebagai bagian dari upaya pencegahan dan penanggulangan ekstremisme kekerasan (P/CVE). Orisinalitas/Nilai – Penelitian ini memberikan salah satu wawasan empiris pertama tentang hubungan antara pekerja migran perempuan dan ekstremisme kekerasan di Indonesia, menyoroti peran strategis mereka sebagai pembangun perdamaian dalam upaya P/CVE.